Beyond compliance? The socio-legal consequences of section 54 of the Modern Slavery Act 2015 - Hsin, K-E (2022)
When s 54 of the Modern Slavery Act was adopted in 2015, it was widely lauded as a breakthrough and a positive step towards holding businesses to account for labour exploitation in global supply chains. But the provision is not prescriptive and light on enforcement. It drew criticism for a lack of enforcement mechanisms and mandatory requirements. But prompted by calls to go ‘beyond compliance’, corporations scrambled to comply. This paradox raises empirical questions about the effects and implications of the provision. As a case study of light-touch regulation, what generalisations, if any, can be drawn from the effects of s 54?